Factores motivacionales presentes en los empleados de la empresa AT&S Montajes - Duque Ramírez, Daniela (Psicología, 2016)
The objective of this research is to measure the overall motivating factor to 58 employees of AT & S company mounts this was done through the application of the test of motivation CMT-Questionnaire Motivation to Work Fernando Toro measuring the following factors: Power, Achievement, Affiliation, Self-Empowerment, Recognition, dedication to the task, the Authority Acceptance, Acceptance of Standards and Values, Requisition, expectation, Supervision, Working Group, Content, salary and promotion. Once applied the following results were obtained: internal motivational conditions as the factor which lowest is scored is self-realization and the highest is recognition on the preferred means to obtain desired remuneration at work the factor lowest scored was acceptance of authority and the highest was requisitioning, in external motivational conditions the lowest factor was work content and the highest salary.